Global impact of COVID-19 on surgeons and team members (GlobalCOST): a cross-sectional study. Issue 8 (5th August 2022) - Jaffry, Zahra; Raj, Siddarth; Sallam, Asser; Lyman, Stephen; Negida, Ahmed; Yiu, Chi Fung Antony; Sobti, Anshul; Bua, Nelson; Field, Richard E; Abdalla, Hassan; Hammad, Rawad; Qazi, Nadeem; et al.
Abstract : Objectives: To investigate the impact of COVID-19 on the well-being of surgeons and allied health professionals as well as the support provided by their institutions. Design: This cross-sectional study involved distributing an online survey through medical organisations, social media platforms and collaborators. Setting: It included all staff based in an operating theatre environment around the world. Participants: 1590 complete responses were received from 54 countries between 15 July and 15 December 2020. The average age of participants was 30–40 years old, 64.9% were men and 32.5% of a white ethnic background. 79.5% were surgeons with the remainder being nurses, assistants, anaesthetists, operating department practitioners or classified other. Main outcome measures: Participants that had experienced any physical illness, changes in mental health, salary or time with family since the start of the pandemic as well as support available based on published recommendations. Results: 32.0% reported becoming physically ill. This was more likely in those with reduced access to personal protective equipment (OR 4.62; CI 2.82 to 7.56; p<0.001) and regular breaks (OR 1.56; CI 1.18 to 2.06; p=0.002). Those with a decrease in salary (29.0%) were more likely to have an increase in anxiety (OR 1.50; CI 1.19 to 1.89; p=0.001) and depression (OR 1.84; CI 1.40 to 2.43; p<0.001) and those who spent less time with family (35.2%) were more likely to have an increase in depression (OR 1.74; CI 1.34 to 2.26; p<0.001). Only 36.0% had easy access to occupational health, 44.0% to mental health services, 16.5% to 24/7 rest facilities and 14.2% to 24/7 food and drink facilities. Fewer measures were available in countries with a low Human Development Index. Conclusions: This work has highlighted a need and strategies to improve conditions for the healthcare workforce, ultimately benefiting patient care.